PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR IPS SISWA KELAS MENENGAH PERTAMA (Studi Eksperimen Siswa Kelas VII SMPN 6 Siak Hulu) - Atikah Adiningrum; Gimin '; RM Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Learning outcomes are the ability students possess once they have received their learning experience, and to determine the outcomes of learning are conducted using tests. Basically student learning outcomes in Economic lessons IPS low. This happens because teachers often use learning methods that are still conventional with dominated lectures that seem monotonous, and the lack of using learning models and learning media. With this research aims to determine the influence of cooperative learning model type examples non examples on the results of learning IPS class VII SMPN 6 Siak Hulu. The population in this study is all students of grade VII SMPN 6 Siak Hulu Kampar regency, amounting to 80 students. While the subjects taken in this study were 54 students. The data of this study were analyzed using lilifors test with significant level α = 0,05. Results of data analysis, in the experimental class obtained an initial average of 75 to 88 on the average final test score. While the control class obtained an average of 66 initial tests and increased to 82 in the final test. The results of data analysis obtained in the study can be concluded that the learning by using the model of learning examples non examples gave a significant effect on the improvement of learning outcomes. The increase did not occur in the experimental class alone but the control class also increased. In this study found the influence of cooperative learning model type examples non examples is 57.43% while 42.57% influenced by other factors. The success of teachers in the learning process can be used as an alternative, and increase the teacher's insight in the use of the model.Keywords: Model of Learning, examples non examples,of Learning outcomes